Localization of Backscatter Transponders Based on a Synthetic Aperture Secondary Radar Imaging Approach - Max, Stephan; Gulden, Peter; Vossiek, Martin (5th IEEE Workshop on Sensor Array and Multi-Channel Signal Processing (SAM 2008), 2008)
In this paper, we introduce the novel synthetic aperture secondary (SAS) radar positioning technique for the localization of a vehicle. The SAS technique is based on a frequency-modulated continuous wave (FMCW) secondary radar concept where the interrogating radar signal is reflected coherently by a backscatter transponder. It will be shown that SAS positioning is a very efficient way to combine the data of wireless positioning systems with the data from assisting sensors. Our novel SAS local positioning technique outperforms the usual integrated or hybrid navigation approaches based on multilateration notably. A 5.8-GHz wireless local positioning system has been built to test our SAS concept. The synthetic aperture is set up by a moving vehicle. Aperture points are determined with the use of gyroscope and tachymeter sensor data. A newly developed SAS reconstruction algorithm estimates the most likely transponder positions. Based on these estimations, the vehicle determines its position with an accuracy of approximately 5 cm even in complex multipath environments. © 2008 IEEE.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.locali